Network-Based Online Survey Exploring Self-Reported Depression Among University and College Students During the Early Days of the COVID-19 Outbreak - Jing, Yurong; Han, Wantong; Wang, Yali; Zhang, Jiao; Qin, Wenzhe; Jing, Xiang; Niu, Aimin; Xu, Lingzhong (Frontiers in Psychiatry, 2021)
Background: The psychology of university and college students is immature, they are thus more likely to suffer from depression due to the COVID-19 pandemic. The present study aims to investigate the self-reported depression status of Chinese university and college students and explore its influencing factors. Methods: We conducted a network-based online survey, and a total of 17,876 participants completed the questionnaire. Depression was measured by the Self-Rating Depression Scale (SDS). Univariate analysis and multivariate logistic analysis were performed to explore the influencing factors of self-reported depression symptoms. Results: The proportion of self-reported depression symptoms, mild self-reported depression symptoms, and moderate to severe (M/S) self-reported depression symptoms was 65.2, 53.7, and 11.5%, respectively. The mean score of self-reported depression was 54.8 ± 9.0. Female, personality type of partial introversion, junior college educational level, “moderate” or “high” self-perceived risk of infection, “moderately” or “highly” impacted by the outbreak, and being eager to go back to school were risk factors for M/S self-reported depression symptoms (p < 0.05). While, “moderate” or “high” concern about the outbreak, “moderate” or “high” satisfaction with pandemic prevention and control measures, and having health literacy on communicable diseases were protective factors for M/S self-reported depression symptoms (p < 0.05). Conclusion: The status of self-reported depression symptoms among university and college students was severer than expected, and the influencing factors were multifaceted. Government and school administrators should strengthen the dissemination of knowledge on disease prevention and control. Moreover, much attention should be paid to female and junior college students.